Nonadherence to Recommended Guidelines for Blood Pressure Measurement. Issue 11 (1st June 2016) - Levy, Jack; Gerber, Linda M.; Wu, Xian; Mann, Samuel J.
Abstract : Accuracy of blood pressure readings, both in the physician's office and at home, is crucial in properly managing hypertension. Few studies have investigated adherence to measurement guidelines. This study focused on two important aspects of blood pressure measurement: waiting time before measurement and number of readings taken. A total of 103 patients completed self‐report questionnaires about office and home blood pressure measurements, with 77% reporting that physician measurements were obtained without waiting, and 56% reporting that only one reading was obtained. The proportions were even higher when measured by a nurse/technician, 96% and 81%, respectively. Home readings were taken without waiting by 60%, and 40% reported taking only a single reading. Most patients received no measurement instructions. Nonadherence to measurement guidelines is common, and may be affecting the validity of readings obtained both in physicians' offices and at home, with significant and potentially harmful effects on treatment decisions.